Cerebrovascular Resistance in Healthy Aging and Mild Cognitive Impairment - McKetton, Larissa; Cohn, Melanie; Tang-Wai, David F.; Sobczyk, Olivia; Duffin, James; Holmes, Kenneth R.; Poublanc, Julien; Sam, Kevin; Crawley, Adrian P.; Venkatraghavan, Lashmi; Fisher, Joseph A.; Mikulis, David J. (Frontiers in Aging Neuroscience, 2019)
Measures of cerebrovascular reactivity (CVR) are used to judge the health of the brain vasculature. In this study, we report the use of several different analyses of BOLD fMRI responses to CO2 to provide a number of metrics of CVR based on the sigmoidal resistance response to CO2. To assess possible differences in these metrics with age, we compiled atlases reflecting voxel-wise means and standard deviations for four different age ranges and for a group of patients with mild cognitive impairment (MCI) and compared them. 67 subjects were recruited for this study and scanned at 3T field strength. Of those, 51 healthy control volunteers between the ages of 18-83 were recruited, and 16 (MCI) subjects between the ages of 61-83 were recruited. Testing was carried out using an automated computer-controlled gas blender to induce hypercapnia in a step and ramp paradigm, while monitoring end-tidal partial pressures of CO2. Surprisingly, some resistance sigmoid parameters in the oldest control group were increased compared to the youngest control group. Resistance amplitude maps showed increases in clusters within the temporal cortex, thalamus, corpus callosum and brainstem, and resistance reserve maps showed increases in clusters within the cingulate cortex, frontal gyrus, and corpus callosum. These findings suggest that some aspects of vascular reactivity in parts of the brain are initially maintained with age but then improve in later years. We found significant reductions in all resistance sigmoid parameters (amplitude, reserve, sensitivity, midpoint, and range) when comparing MCI patients to controls. Additionally, in controls and in MCI patients, amplitude, range, reserve, and sensitivity in white matter (WM) was significantly reduced compared to gray matter (GM). WM midpoints were significantly above those of GM. Our general conclusion is that, vascular regulation in terms of cerebral blood flow responsiveness to CO2 is not significantly affected by age, but does start to decline in MCI. These findings, detailing changes in cerebrovascular regulation of resistance in healthy individuals with age and in MCI, demonstrate the value of resistance metrics for mapping areas of dysregulated blood flow in individuals with vascular risk factors, especially those at risk for developing vascular dementia.